2006
DOI: 10.4049/jimmunol.177.4.2051
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibition of TLR and FcR Responses in Macrophages by Triggering Receptor Expressed on Myeloid Cells (TREM)-2 and DAP12

Abstract: DAP12 is an ITAM-containing adapter that associates with receptors in myeloid and NK cells. DAP12-associated receptors can give activation signals leading to cytokine production; however, in some situations, DAP12 inhibits cytokine production stimulated through TLRs and FcRs. Here we show that Triggering Receptor Expressed on Myeloid cells (TREM)-2 is responsible for the DAP12-mediated inhibition in mouse macrophages. A chimeric receptor composed of the extracellular domain of TREM-2 and the cytoplasmic domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
370
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(382 citation statements)
references
References 20 publications
11
370
1
Order By: Relevance
“…Besides inhibiting other ITAM-bearing receptors, as previously shown (20), we found that responses induced by a highly diverse set of inflammatory mediators such as MCP-1, TNF-␣, and LPS were inhibited. The homologous ITAM-bearing adaptor DAP12, when associated with the isoform TREM-2, has also been found to down-regulate activating responses triggered via TLRs and Fc receptor (21,22). Interestingly, incubation with anti-Fc␣RI Fab before stimulation with IgA immune complex present in serum of IgA nephropathy patients also attenuated activation induced by its own receptor.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides inhibiting other ITAM-bearing receptors, as previously shown (20), we found that responses induced by a highly diverse set of inflammatory mediators such as MCP-1, TNF-␣, and LPS were inhibited. The homologous ITAM-bearing adaptor DAP12, when associated with the isoform TREM-2, has also been found to down-regulate activating responses triggered via TLRs and Fc receptor (21,22). Interestingly, incubation with anti-Fc␣RI Fab before stimulation with IgA immune complex present in serum of IgA nephropathy patients also attenuated activation induced by its own receptor.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanism involves an inhibitory ITAM (ITAM i ) function of the associated FcR␥ adaptor. Similar ITAM i -mediated inhibition has been described with another ITAM-bearing adaptor, DAP12, in association with triggering receptor expressed on myeloid cell (TREM)-2 or with Siglec-H (21)(22)(23).…”
mentioning
confidence: 85%
“…This suggests that the ligation of TREM-2 by gonococci mediates signal transduction through a functional molecular complex of DAP12 and TREM-2 which may play a role in the innate immune response of human reproductive tract epithelial cells to gonococcal infection. However, unlike TREM-1 which amplifies the inflammatory response to bacteria through the production of proinflammatory cytokines and chemokines when engaged (21,24), ligation of TREM-2 results in upregulation of certain receptors such as CCR7, CD40, and CD86 on dendritic cells (48), but inhibition of TLR receptor responses such as TNF production in macrophages (52). A similar inhibitory response mediated by TREM-2 expressed by myeloid cell types in the human genitourinary tract may contribute to the limited cytokine responses seen in uncomplicated cervical gonococcal infection (53).…”
Section: Discussionmentioning
confidence: 99%
“…The TREM2/ TYROBP complex is reported to regulate key signaling pathways involved in differentiation of dendritic cells and osteoclasts, phagocytic activity in microglia and immune responses (Bouchon et al 2001;Hsieh et al 2009;Otero et al 2012). In the CNS, it is revealed that TREM2 negatively regulates inflammatory responses by repression of cytokine production and secretion in response to both TLR2 and TLR4 ligands zymosan and LPS (Hamerman et al 2006;Sessa et al 2004;Turnbull et al 2006). Therefore, TREM2 is speculated to be beneficial in AD pathogenesis (Fig.…”
Section: Trem2mentioning
confidence: 99%